Impact of group antenatal care on lactational amenorrhea method awareness and knowledge: A cluster randomized control trial - Theresa Norpeli Lanyo; John E. O. Williams; Bidisha Ghosh; Veronica E. A. Apetorgbor; Vida A. Kukula; Ruth Zielinski; Elizabeth Awini; Cheryl A. Moyer; Jody Lori (PLoS ONE, 2025)
High fertility rates in low and middle-income countries (LMICs), especially in sub-Saharan Africa and Ghana, lead to closely spaced pregnancies and contribute to high maternal and infant morbidity and mortality. Family planning remains critical for reducing rapid repeat and unwanted pregnancies, thus improving the health and survival outcomes. Unfortunately, many women face significant unmet needs due to limited knowledge, misinformation, and limited access to modern family planning methods in particular. Breastfeeding plays a substantial role, and the lactational amenorrhea method (LAM) offers a practical, natural, readily available, and cost-efficient postpartum option when practiced correctly. However, many mothers lack sufficient awareness of LAM and the conditions necessary for its effectiveness. Antenatal care provides a strategic opportunity for targeted education and counselling on contraceptive choices, empowering women with the knowledge to adopt safe, informed, and sustainable practices. Group antenatal care (G-ANC), recommended by WHO for research in LMICs, offers a comprehensive and participatory platform for health education and behavioral change. This study examined G-ANC and its impact on creating awareness and improving knowledge of the lactational amenorrhea method among mothers. A cluster randomized control trial, registered at ClinicalTrials.gov on 25/07/2019 with RCT number NCT04033003, was conducted in Ghana at 14 health facilities with a total of 1761 participants. The study included pregnant women who were at least 15 years old, able to speak English or one of four local languages, and less than 20 weeks of gestation at enrollment. Women classified as high-risk by the midwife were excluded from participation in the study. Facilities were randomized using a matched pair method. Structured interviews were conducted at baseline and subsequent timepoints. The results found that group antenatal care increases maternal awareness and knowledge of the postpartum lactational amenorrhea method of family planning compared to individualized care. Subgroup analysis revealed that a mother’s level of education and parity strongly predict maternal awareness of the lactational amenorrhea method. These findings support group antenatal care as an effective strategy to improve knowledge on the use of lactational amenorrhea as a family planning method.